How Does Taching Look Like in Reality? (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Teaching is a honorable profession that plays a crucial role in contributing to the futures of most individuals. Educators are the great source of motivation, inspiration and empowerment of students to reach their full potential. This article will discuss the art of teaching, highlighting the prime principles, strategies, and difficulties faced by educators in today’s fast-moving educational landscape. The given article gives information about the role of a teacher, strategies that are used by teachers and challenges they face working with a variety of students.